Ziele bei der Entwicklung des Hörverstehens im Germanistikstudium - MYCZKO, Kazimiera (Wydawcnictwo Naukowe UAM, 1994)
Listening with understanding is one of the most difficult skills in foreign language teaching and learning. This skill must be intensively developed during the philology study. The author presents some considerations on receptive competence and the conditions of it. In the last part of the paper are given the aims to attain by German philology students at the middle and advanced levels.